Preparation of SrBi2Ta2O9 ferroelectric thick films by electrophoretic deposition using aqueous suspensions - Zanetti, S. M.; Varela, José Arana [UNESP]; Leite, E. R.; Longo, Elson [UNESP] (Amer Ceramic Soc, 2003)
SrBi2Ta2O9 ferroelectric thick films were prepared by electrophoretic deposition (EPD). For that, ceramic powders were prepared by chemical method in order to obtain compounds with chemical homogeneity. The polymeric precursor method was used for the synthesis of the SrBi2Ta2O9 powder. The crystallographic structure of the powder was examined by X-ray diffraction, and the surface area was determined by single point BET adsorption. The 0.03 vol% suspension was formed by dispersing the powder in water using two different polymers as dispersants: an ester polyphosphate (C213) and an ammonium polyacrilate (Darvan 821-A). The influence of the different dispersants on the powder surface properties were investigated by zeta potential measurements. The films were deposited on platinum-coated alumina and Pt/Ti/SiO2/Si substrates by electrophoretic deposition using a 4 mA constant current, for 10 min, with two parallel electrodes placed at a separation distance of 3 min in the suspension. Several cycles of deposition-drying of the deposit was carried out until the desired thickness was obtained. After thermal treatment at temperatures ranging from 700 to 1000degreesC, the films were characterized by X-ray diffraction and scanning electron microscopy.